Community pharmacists' patient counselling in Tasmania towards patient-oriented care - Robles, Yolanda R.
Pharmaceutical care is the new philosophy and mission of the pharmacy profession which is responsive and relevant to the changing health care priorities and problems associated with drug use in the 1990s. It is expected that this patient-oriented practice will enhance the contribution of the profession to positive health outcomes. However, the adoption of this ideal practice has been observed to be more consistent at the institutional level, rather than at the community setting. Numerous factors inherent to the community setting, hindering its wider implementation, are implicated in the literature. Of the major activities performed under pharmaceutical care, pharmacists were found to perform poorly in roles requiring active interaction with patients, particularly patient counselling. It was revealed in several studies such as a recent North American review, that there had been no substantial improvement in the quantity and relative quality of pharmacists' patient communication during the past 25 years. This grim assessment of pharmacists' performance in patient counselling has become a paradox in view of the clinical orientation in pharmacy education, government support and other reinforcing features of the community practice setting in Western countries. While this concern has been repeatedly addressed by various sectors in the profession through practice and education interventions, the re-examination of current philosophical and methodological issues in pharmacy practice research has been recently advocated and the consideration of their alternatives suggested in order to ascertain the real issues confronting pharmacists' counselling practice. The main objectives of the present work are 1) to develop a research methodology which will help generate a better underestanding of the subjective and contextual aspects of community pharmacists' patient counselling; 2) to design a specific educational intervention and its workplace evaluation based on the findings of training needs assessment and contextual analysis and 3) to identify the factors which affect the application of learning to the workplace within the practice context of community pharmacists in Tasmania. Preceded by a review of the social aspects of drug therapy in health care and the current state of pharmacists' patient counselling, this work critically examine and evaluates paradigms, approaches and methods on the basis of their appropriateness and applicability to current issues affecting pharmacists' patient counselling. From this analysis, a research framework and its methodology were designed and used in conducting training needs assessment and situational analysis covering some general and specific aspects of patient counselling by community pharmacists in Tasmania, particularly the counselling of non-insulin dependent diabetes mellitus (NIDDM) patients. A combination of methods, mostly qualitative, were used to gather pertinent data from the perspectives and experiences of community pharmacists, NIDDM patients and key health professionals.